Endoscopic ultrasound in the follow up and response assessment of patients with primary gastric lymphoma. Issue 5 (1st November 2002) - Püspök, A; Raderer, M; Chott, A; Dragosics, B; Gangl, A; Schöfl, R
Abstract : Background: Endoscopic ultrasound (EUS) is considered the best technique for local staging of primary gastric lymphomas. Its role in the follow up of patients with gastric lymphoma following organ conserving strategies has not been established. Aim: To compare endosonographic response assessment with results of histological evaluation. Patients and methods: Thirty three patients with primary gastric lymphomas underwent pretreatment EUS and were followed endosonographically every 3–6 months after administration of organ conserving treatment modalities. A wall thickness of ≤4 mm with preserved five layer structure and the absence of suspicious lymph nodes was defined as endosonographic remission. Decrease in wall thickness, increase in echogenicity, and regression of lymph nodes were tested for their value to predict histological remission. Results: A total of 158 endosonographies were performed (median 4; range 2–12). Within a median follow up period of 15 months (range 3–48), 27 (82%) patients achieved complete histological remission while endosonographic remission was found in 21 (64%) patients. Eighteen patients achieved both forms of remission, with endosonographic remission occurring later (35.1 (11–212.9) weeks v 17.6 (11–97.9) weeks; median (range); p<0.02) than histological remission. A further three patients demonstrated a false negative remission on EUS. Histological relapse was paralleled by endosonographic relapse in only one of five patients. None of the tested endosonographic parameters was able to predict histological remission. Conclusions: In view of the inferior accuracy of EUS when compared with histology, gastroscopy with biopsy seems sufficient for the routine follow up of patients with gastric lymphoma.